ESTIMATION OF POTENTIAL AND EFFECTIVE BR?NSTED ACID SITE CONCENTRATIONS IN ACIDIC MORDENITES BY CONDUCTOMETRIC TITRATION METHOD (Journal of Sciences, Islamic Republic of Iran)
Quantitative determination of Br?nsted acid sites in acidic mordenite samples with varying proton concentrations has been studied using aqueous conductometric titration method. Conductometric titration of the ammonium form of mordenite with sodium hydroxide is feasible and the results indicate potential number of Br?nsted acid sites. However, Br?nsted acid sites concentration in acidic mordenites, measured by this method, is less than that evaluated by ammonium-mordenite titration. Calcination procedure, to produce acidic mordenites from its ammonium form, reduces Br?nsted acid sites by dealumination and dehydroxylation processes. In conductometric titration, only accessible Br?nsted acid sites are titrated and extra-framework aluminum species, which are generated during calcination and reside in the structure, are not titrated. This finding is supported by observing more reduction in the Br?nsted acidity when higher temperatures of calcination are employed. Also, comparing diffuse reflectance spectra of the acidic mordenite before and after titration does not show extra-framework aluminum species reacting with added base. A negative linear correlation was observed between concentration of Br?nsted acid sites measured by conductometric titration and the temperature of calcination within 450-750°C.